Notes of a participatory action research experience (2021)
This article pretends to show how in the context of a Participatory Action Research process, the methodological part constitutes an exercise that enhances learning for the group leaders and residents of the community, and for the research team of the University. The practical approach versatility and its force are highlighted as a vehicle of empowerment for local development. It concludes that this empowerment framework and emergency capacity is the opportunity to emerge, from the residents and the community environment, protection and prevention factors for the exploitation and sexual abuse of children.